ANALYSIS OF THE ENGLISH LANGUAGE CURRICULUM FOR THE FOURTH GRADE OF MIDDLE SCHOOL, AN EVALUATIVE STUDY - Hamdan, Faraj Mashhad (Journal of Higher Education and Academic Advancement, 2024)
The study sought to determine the quality of the English language curriculum for the fourth grade of middle school in Iraqi schools by adopting standards related to objectives, vocabulary, activities, exercises, content, and artistic direction. The study adopted the descriptive approach through the content analysis method through a form designed by the researcher. The results of the study showed: 1. The general objectives of the English language curriculum for the fourth grade of middle school are characterized by clarity and focus on the procedural form of objectives. 2. The content of the curriculum focused on adopting the objective grouping of ideas and vocabulary.